Revisiting the Razak Report 1956 as a historical educational text: a critical historical analysis - Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The growth and development of the Malaysian education system has been very colorful, in which it is full of interesting events and changes that strived towards the betterment of the people of Malaysia from the time of Western colonization up to now. Even though Malaysia has only been an independent nation for only about 56 years from the British Empire, the education system in Malaysia has been created, contorted, and revamped numerous times in accordance to the goals of the nation and the needs of the people of Malaysia. Within these numerous occasions of change of the Malaysian educational structure, the most prominent event is the development and implementation of the Report of the Education Committee 1956, or better known as the Razak Report 1956. Even until now the Razak Report 1956 continues to be the most important educational structure to be developed and implemented because it managed to provide a comprehensive educational structure for all three major ethnic groups in Malaysia (i.e., Malays, Chinese, and Indians). More importantly, even though the development and implementation of this educational plan was not without concerns and questions by these three ethnic groups, it managed to bring these three ethnic groups together in gaining independence from the British Empire and helped them develop a nation that they can call their home regardless of their social and cultural differences.